Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance
The standard can be bought from this web page.

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité
La norme peut être achetée à partir de cette page web.

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)